Pelatihan Pengolahan Produk Berbahan Dasar Rumput Laut Di Kelurahan Sarae - sri ernawati; M. Yusuf; Rujalil Rujalil; Katarina Katarina (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2021)
This community service activity is the provision of training on processing seaweed-based products. The participants of this training activity are mothers of productive age and teenagers. The purpose of this training on processing seaweed-based products is that the community is able to process seaweed into high-value innovation products so that they can help the household economy of the trainees. The training was conducted for 1 day in the Sarae Village office hall. The results of the activity showed that the participants understood the training provided. The success is shown by the positive response from the participants, by being directly involved in the process of processing seaweed into lunkhead and rengginang as well as the packaging process of processed products.